Cell proliferation of colonic neoplasms in dimethylhydrazine-treated rats. - Sunter, J. P. (Nature Publishing Group, 1980)
We have measured mitotic indices and 3H-thymidine-labelling indices for the colonic epithelial tumours induced in rats by the administration of dimethyl-hydrazine (DMH). The fraction-of-labelled-mitoses (FLM) technique has been used to estimate the duration of the cell-cycle phases. In general, mitotic and labelling indices in the tumours are similar to those in the proliferation zone of the normal crypt epithelium; lesions considered to be least well differentiated on histological grounds appear to have the lowest mean labelling index. Benign tumours and the different types of malignant tumours have mean cell-cycle times about half those of the normal mucosa.